2021
DOI: 10.1007/s10570-021-04070-8
|View full text |Cite
|
Sign up to set email alerts
|

Directional synthesis of furfural compounds from holocellulose catalyzed by sulfamic acid

Abstract: The coproduction of 5-hydroxymethylfurfural (5-HMF) and furfural (FUR) via the direct hydrolysis of holocellulose analogue composed of cellulose and hemicellulose was investigated. The effects of catalyst amount, solvent type and amount, reaction temperature and time using sulfamic acid with dual active sites as catalyst were also studied. The yields of 5-HMF and FUR at 37.2% and 62.0% were obtained with the volume ratio of γ-valerolactone to water of 25:1 at 180 o C for 3 h. The conversion of corn cob holocel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Under the high temperature of 190 °C, HMF concentration was reduced from 45.6 to 36.7 mM as the reaction time was raised from 40 to 100 min. Due to potential side reactions, high temperature or long dehydration duration will lead to the degradation of the prepared HMF to other byproducts (humus and levulinic acid), thus reducing the output of HMF . Therefore, the highest dehydration activity was detected at 170 °C for 80 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the high temperature of 190 °C, HMF concentration was reduced from 45.6 to 36.7 mM as the reaction time was raised from 40 to 100 min. Due to potential side reactions, high temperature or long dehydration duration will lead to the degradation of the prepared HMF to other byproducts (humus and levulinic acid), thus reducing the output of HMF . Therefore, the highest dehydration activity was detected at 170 °C for 80 min.…”
Section: Resultsmentioning
confidence: 99%
“…Due to potential side reactions, high temperature or long dehydration duration will lead to the degradation of the prepared HMF to other byproducts (humus and levulinic acid), thus reducing the output of HMF. 40 Therefore, the highest dehydration activity was detected at 170 °C for 80 min. In the catalytic medium, the addition amount of BW will affect the chemocatalytic efficiency.…”
Section: Acs Sustainable Chemistrymentioning
confidence: 93%
“…SA (50% w/w) was also investigated as a bifunctional catalyst for the hydrolysis of holocellulose, which is composed of cellulose and hemicellulose, in a solvent medium comprising γ-verolactone and water (25:1 v/v) [30]. Under autoclave conditions (1 MPa) at 180 • C and in an inert N 2 atmosphere, 5-HMF and furan were obtained with 37.2% and 62.0% yields, respectively (HPLC yield), after 3 h. Comparative experiments revealed that Brønsted acids, such as H 2 SO 4 and Amberlyst acid resins, furnished only traces of 5-HMF under the same reaction conditions.…”
Section: -Hydroxymethylfurfural (5-hmfmentioning
confidence: 99%